IOT Based Vehicle Speed Control Automatically in Restricted Areas using RFID - N. V. Satyanarayana, K; Yaswanthini, G; L. Kartheeka, P; Rajkumar, N (International Journal of Engineering and Technology, 2018)
Now-a-days road accidents are occurring frequently, due to rash driving of people.Â The most unfortunate thing is that by making small mistakes during driving, we lost our valuable future. If we observe, most of the accidents will occur at school zones, parks, hospitals, hill areas and highways. Even a police also canâ€™t monitor all such kind of accidents. So in order to reduce the number of accidents and to control the vehicle speed the highway department has placed the signboards. But it is difficult to observe such kind of signboards and hence accidents will occur. This paper will provide a new way for controlling the speed of the vehicle without harming others. In this paper, we are using RFID module to limit vehicle speed. The RF transmitter will be placed at first and last of the restricted areas and RFID receiver should be placed inside the vehicle. The vehicle speed was obtained by speedometer which is available in vehicle. And that speed is compared and monitored by the controller. If the vehicle speed exceeds the limited speed, It automatically controls the speed of the vehicle according to that particular zone. Hence, automatically the speed reduced. If there is any emergency, a switch will be available in the vehicle. When the switch is ON, the speed is not controlled automatically. The vehicle which is switched ON, that vehicle number was stored in cloud. Here the main purpose of cloud is it loads the route map of the vehicle.Â Â